2016
DOI: 10.2119/molmed.2016.00017
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Dimethylacetamide Significantly Attenuates LPS- and TNFα-Induced Proinflammatory Responses Via Inhibition of the Nuclear Factor Kappa B Pathway

Abstract: Previously, we have shown that N,N-dimethylacetamide (DMA) prevents inflammation-induced preterm birth in a murine model, inhibits lipopolysaccharide (LPS)-induced increases in placental proinflammatory cytokines and upregulates the antiinflammatory cytokine interleukin-10 (IL-10). However, DMA's mechanism of action remains to be elucidated. In the current study, we investigate how DMA produces its antiinflammatory effect. Using in vitro and ex vivo models, we show that DMA suppresses secretion of proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 80 publications
4
31
0
Order By: Relevance
“…When DMA was added along with the MCT, the decrease in TNF-α was found to be 60%, showing that DMA further decreased the release of TNF-α. Our results are in agreement with previously reported results showing that DMA inhibits TNF-α release [24,25]. The reduction of cytokine release produced by the MCT and DMA may further enhance the formulation’s efficacy in preventing PTB.…”
Section: Resultssupporting
confidence: 93%
“…When DMA was added along with the MCT, the decrease in TNF-α was found to be 60%, showing that DMA further decreased the release of TNF-α. Our results are in agreement with previously reported results showing that DMA inhibits TNF-α release [24,25]. The reduction of cytokine release produced by the MCT and DMA may further enhance the formulation’s efficacy in preventing PTB.…”
Section: Resultssupporting
confidence: 93%
“…Also, proinflammatory cytokines, such as IL‐1β and TNF‐α, stimulate iNOS expression through NF‐κB . Inhibition of the NF‐κB pathway can be considered as a possible mechanism for reducing cytokine expression and NO production, as previously described with LPS‐stimulated RAW 264.7 cells . The reduction in these cytokine levels in LPS‐stimulated macrophage, by Fr3 and Fr4, may also be related to inhibition of p38 MAPK as this kinase inhibition has been related to the inhibition mechanism of IL‐β 1 and TNF‐α production for the diterpene lobolide .…”
Section: Discussionmentioning
confidence: 82%
“…The present study showed that the reduction of IL‐1 β, TNF‐α, IL‐10 and iNOS, in LPS‐stimulated RAW 264.7 macrophages, is probably due to, among other effects, the inhibition of the expressions of these proteins at the mRNA level. Also, proinflammatory cytokines, such as IL‐1β and TNF‐α, stimulate iNOS expression through NF‐κB . Inhibition of the NF‐κB pathway can be considered as a possible mechanism for reducing cytokine expression and NO production, as previously described with LPS‐stimulated RAW 264.7 cells .…”
Section: Discussionmentioning
confidence: 88%
“…NF-kB is a pleiotropic transcription factor that increases proinflammatory cytokine production, and regulation of its activation is therefore considered one of the approaches to reduce the risk of PTB [ 33 , 34 , 35 ]. Novel therapeutics that reduce inflammation by inhibiting NF-kB using anti-inflammatory drugs [ 36 , 37 , 38 ], cell-penetrating peptides, small molecule inhibitors [ 33 , 39 , 40 ], nonspecific inhibitors [ 41 , 42 , 43 , 44 ], and flavonoids are now being tested [ 45 , 46 ]. However, very few have made it to clinical trials so far and none are in use clinically, likely due to several issues including, but not limited to, the mode of delivery, placental permeability, teratogenicity, and transgenerational effects.…”
Section: Discussionmentioning
confidence: 99%